A New Perspective to Algebraic Characterization on Controllability of Multiagent Systems. (27th March 2020) - Liu, Bo; Su, Housheng; Wu, Licheng; He, Shengchao
Abstract : Recently, algebraic characterization of multiagent controllability through its topology has been widely concerned by the systems and control community. The controllability of leader-follower networked multiagent systems under the framework of generic linear dynamics is firstly discussed via λ -matrix. Some new algebra-theoretic necessary and/or sufficient conditions of the controllability for generic linear multiagent systems are established. Moreover, the controllable conditions for multiagent networks with special topological graphs through λ -matrix are presented.